Identitas Diri Sebagai Muslimah dan Intensi Memakai Jilbab pada Mahasiswi - Noviany, Rori Saprita (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2004)
The current study is focused on finding a relationship between self identity as Muslim women and the intention to wear hijab. The hypothesis of this study there is a relationship between self identity as Muslim and the intention to wear hijab. The more positive the self identity as Muslim the stronger the intention to wear hijab. The sample of this study were 200 students from one private university in Yogyakarta. The two variables were measured using self identity scale and intention to wear hijab scale. The results confirms the hypothesis (r = .595, pKey Words: Self identity as Muslim, Intention, Hijab